(untitled) (Journal on studies and research of academic knowledge, 2016)
The general objective to this study is to "Determine whether the academic offer of the Bachelor in Management FACEA UNI meets the demands of the labor market", this non experimental research, quantitative and qualitative; cross, descriptive, developed at the Faculty of Economics and Administrative Sciences (FACEA) of the National University of Itapúa, in the city of Encarnación. The analysis unit made up of 87 graduates, 36 teachers, 3 directors of the race, between the years 2008 2014 and 20 representatives of employer firms in the region. Questionnaires were used with open and closed questions categories. Although the instruments used were distributed to the entire universe, he answers 80% of graduates and teachers of the race I had to; 100% of managers and 20 representatives of employer firms. The research concludes that: Virtually all (87) of the Professional Graduates are embedded within most representative companies and institutions in the region, carrying out managerial and administrative functions. The perception of Professional Teachers Graduates and respondents on the relevance of the graduate profile (2004) relative to the profile required by the labor market is "partly right"; while most employers perceive it as "entirely appropriate" and in smaller percentage "partly right" with significant weaknesses identified by them. It is considered appropriate redirect to turn these weaknesses into strengths.